2015
DOI: 10.1063/1.4913367
|View full text |Cite
|
Sign up to set email alerts
|

Surface protein gradients generated in sealed microchannels using spatially varying helium microplasma

Abstract: Spatially varied surface treatment of a fluorescently labeled Bovine Serum Albumin (BSA) protein, on the walls of a closed (sealed) microchannel is achieved via a well-defined gradient in plasma intensity. The microchips comprised a microchannel positioned in-between two microelectrodes (embedded in the chip) with a variable electrode separation along the length of the channel. The channel and electrodes were 50 μm and 100 μm wide, respectively, 50 μm deep, and adjacent to the channel for a length of 18 mm. Th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
5
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 49 publications
2
5
0
Order By: Relevance
“…This expansion of the discharge glow along the microchannel is consistent with the gradual purging of air with He in the microchannel. It can be concluded that the gradual decrease of light emission along the microchannel, observed in our previous work, is from a He discharge. The rapid decrease of the light emission along the microchannel in this work is from a discharge with an air–He mixture.…”
Section: Discussionsupporting
confidence: 55%
See 4 more Smart Citations
“…This expansion of the discharge glow along the microchannel is consistent with the gradual purging of air with He in the microchannel. It can be concluded that the gradual decrease of light emission along the microchannel, observed in our previous work, is from a He discharge. The rapid decrease of the light emission along the microchannel in this work is from a discharge with an air–He mixture.…”
Section: Discussionsupporting
confidence: 55%
“…Comparison of the plasma intensity profile along the microchannel in our previous work (Figure a, d = 150 μm) with this study (Figure ) shows a significant difference. In our previous work, the total light intensity (normalised to the intensity at the narrow end of the microchannel) decreases steadily along the microchannel reaching a value of around 0.15 (relative intensity).…”
Section: Discussionsupporting
confidence: 48%
See 3 more Smart Citations